CHIKUNGUNYA-ASSOCIATED UVEITIS AND EXUDATIVE RETINAL DETACHMENT: A CASE REPORT. Issue Volume 9:Issues 4(2015:Autumn) (2015) - Scripsema, Nicole K.; Sharifi, Emile; Samson, C. Michael; Kedhar, Sanjay; Rosen, Richard B.
Abstract : Purpose: To report the first known case of bilateral granulomatous panuveitis secondary to chikungunya fever in the United States, acquired by a U.S. citizen traveling from an endemic region. Methods: Case report. Results: A 47-year-old woman presented with 10 days of bilateral decreased vision and photophobia concurrent with a febrile illness contracted while visiting the Dominican Republic. She presented with bilateral granulomatous panuveitis and exudative retinal detachments. Extensive workup was negative with the exception of positive chikungunya virus immunoglobulin G and immunoglobulin M titers. Initially, she responded to corticosteroid treatment but developed recurrent inflammation 3 months after completing the initial treatment. Immunomodulatory therapy was initiated at the time of recurrence, and with immunomodulatory therapy alone her inflammation has been controlled for 6 months. Conclusion: The prevalence of chikungunya fever–related uveitis is increasing with the recent epidemics throughout the Americas. Inflammation can occur during the febrile illness or months later and can manifest in a variety of ways. Posterior segment inflammation is more commonly a delayed presentation. Previous reports suggest that chikungunya fever–related uveitis responds well to corticosteroid therapy. This is the first reported case of recurrent inflammation. Given the wide variety of presentations, chikungunya fever–related uveitis should be included in the differential diagnosis of all at-risk patients presenting with acute ocular inflammation, particularly those traveling from endemic regions. Abstract : The purpose of this case report is to establish the presence of chikungunya fever–related uveitis in the United States acquired by a citizen traveling from an endemic region, to demonstrate an unusual clinical presentation, and to report the first known case of recurrent inflammation.